Sosialisasi Dampak Penggunaan Smartphone Terhadap Siswa Siswi Mts Ittihadiyah Karang Dapo Musi Rawas Utara - Deni Apriadi; Alfiarini; Robi Yanto (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
The rise of smartphone users or smart phones is increasingly widespread in various circles, not to mention smartphone users from among students of various ages. This is inseparable from the impact of the COVID-19 pandemic, which requires all schools to conduct online learning, from Kindergarten (TK), Elementary School, Junior High School and Middle School and above or equivalent. Starting from the need for smartphones for the benefit of student learning, but ended with the misuse of smartphones that were used to access negative things that had an impact on students. MTS Ittihadiyah Karang Dapo is one of the schools that implement online learning. 82% of students have a smartphone and 20% do not have a smartphone. From the survey results, 91% of students are not supervised by their parents in using smartphones. After taking the pre-test, 85% of students do not know the impact that arises from the use of smartphones. After following the socialization and doing a post test, there was an increase in understanding of the impact of using a smartphone.